2003
DOI: 10.3152/147154403781776708
|View full text |Cite
|
Sign up to set email alerts
|

Service marks as novel innovation indicator

Abstract: The analysis of services is difficult, due to a lack of appropriate statistical data. In this context, service marks prove to be an interesting novel indicator, showing a significant correlation to innovation. They allow the examination of structures and specialisation in service subsectors, in particular with regard to knowledge-intensive services. Furthermore, it is possible to analyse the area of product-accompanying services in more detail. The recent introduction of European marks has considerably improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 2 publications
3
87
0
6
Order By: Relevance
“…In his study, Schmoch (2003) finds a highly significant correlation between innovation and trademarks, namely in the manufacturing sector. Focusing on service trademarks, he found considerable differences between sectors, namely in the case of knowledge-intensive services.…”
Section: Insert Table 2 Herementioning
confidence: 96%
See 1 more Smart Citation
“…In his study, Schmoch (2003) finds a highly significant correlation between innovation and trademarks, namely in the manufacturing sector. Focusing on service trademarks, he found considerable differences between sectors, namely in the case of knowledge-intensive services.…”
Section: Insert Table 2 Herementioning
confidence: 96%
“…In a recent study, Schmoch (2003) also highlighted the suitability of trademarks as an indicator of innovation. Specifically, he argues that "they meet essential preconditions, in particular correlation to innovation, good data access by electronic databases, and the possibility of operationalising them in relevant dimensions of desegregation" (p. 155).…”
Section: Trademarks As An Indicator In Recent Studiesmentioning
confidence: 99%
“…Interestingly, there is some evidence suggesting that trademarking is associated to innovation, in particular in the service industry. A few examples include Schmoch (2003) who has found that trademarks and product innovation are positively correlated in the service industry and Malmberg (2005) who compared the new trademark applications with the launch of new product innovations and found that there is a positive correlation between the two in particular among companies targeting consumers.…”
Section: Can Trademarking Influence Total Factor Productivity?mentioning
confidence: 99%
“…which makes distinctive the goods or services offered by a firm. Trademarks belong to the portfolio of legal mechanisms which protect a firm's intellectual property and have been mostly studied as such in conjunction with patents, design rights and so on (Schmoch, 2003;Greenhalgh and Rogers, 2005). However, economists have pointed out that they perform other roles: for instance, it has been suggested that firms use them to differentiate their products from those offered by their competitors (Landes and Posner, 1987;Elliott and Percy, 2006); also, they can signal consumers that the products on sale are of consistent quality contributing to solve the problem of asymmetric information between producers and consumers about the quality of the products.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that reference to prior experiences is particularly valuable for customers when (service) production is interactive and intangible (Schmoch, 2003;Lemley, 1999). Hence, trademarks should diminish the ease of product substitutability in knowledge-intensive service sectors.…”
Section: Introductionmentioning
confidence: 99%